DAMPAK GAME ONLINE PADA INTERAKSI SOSIAL PESERTA DIDIK SEKOLAH DASAR - Tominikus Veri; Thomas Joni Verawanto Aristo; Imanuel Sairo Awang (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
This research is motivated by student interest in online games to the extent that students are more likely to play online games than interact with friends. The research is aims to describe the impact of online games on social interaction. The method conducted by descriptive analysis the design is case study research. The data collection technique uses interviews, observation, and documentation. The data analysis technique used is the Miles and Huberman Model data analysis technique, namely: data collection, data reduction, data display, and conclusion. The results of this study indicate that: First, the positive impact of online games on students' social interactions, namely being able to improve English skills, getting to know new technology from a game, and interacting with many friends in the game even though virtually. Second, the negative impact of online games on students' social interactions, namely, they tend to play online games rather than interact with their peers, become lazy to study, like to be individualists, or be alone in their rooms playing online games. Third, students' social interactions as an impact of playing online games, namely games cause forgetting of time, students or children tend to choose to play games over other activities, feel limited friends, social interactions become worse by playing games (angry, toxic), become empathetic towards friends playing online games. Second is the negative impact of online games on students' social interactions, namely social changes. Third, students' social interactions as an impact of online games, namely students or children, tend to choose to play games over other activities.